1984
DOI: 10.1111/j.1365-2125.1984.tb05007.x
|View full text |Cite
|
Sign up to set email alerts
|

Should we routinely measure free plasma phenytoin concentration?

Abstract: The plasma protein binding of phenytoin was investigated in 56 epileptic patients attending the outpatient clinc. The free phenytoin fraction was measured by equilibrium dialysis at 37°C and the total concentration by a homogenous enzyme immunoassay technique. The free fraction ranged from 0.123 to 0.177 (median 0.144, mean + s.d. = 0.145 + 0.012). Distribution was consistent with normality. Four of the patients were also taking sodium valproate. The median free fraction of phenytoin in these patients was 0.17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

1984
1984
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…Routine monitoring of total plasma PHT concentrations helps clinicians in optimizing the treatment of epileptic patients. 1 However, the measurement of free PHT concentration is more important because a slight fluctuation of the protein-binding ratio results in a marked change in free fraction of drug, especially seen in conditions like hypoalbuminemia caused by undernourishment, burns, and so on. 2 Hypoalbuminemia conditions that lead to decreases in availability of plasma albumin thereby increase the free PHT fraction.…”
Section: Introductionmentioning
confidence: 99%
“…Routine monitoring of total plasma PHT concentrations helps clinicians in optimizing the treatment of epileptic patients. 1 However, the measurement of free PHT concentration is more important because a slight fluctuation of the protein-binding ratio results in a marked change in free fraction of drug, especially seen in conditions like hypoalbuminemia caused by undernourishment, burns, and so on. 2 Hypoalbuminemia conditions that lead to decreases in availability of plasma albumin thereby increase the free PHT fraction.…”
Section: Introductionmentioning
confidence: 99%
“…We (Peterson et al, 1982) had previously found a much wider range of free phenytoin fractions (0.097 to 0.247) in 100 epileptic patients. Rimmer et al (1984) were unable to explain this discrepancy, but suggested we may have had methodological problems. In fact, however, our methods were very similar.…”
Section: Monitoring Free Plasma Concentrations Of Phenytoinmentioning
confidence: 92%
“…Rimmer et al (1984) did not provide details of how their patient sample was selected from outpatient clinics. None of their patients had evidence of renal or hepatic dysfunction, all had normal plasma albumin levels, and only four were receiving a displacing drug (sodium valproate).…”
Section: Monitoring Free Plasma Concentrations Of Phenytoinmentioning
confidence: 99%
“…In otherwise healthy epileptic palients, phenytoin is approximately 90% protein bound in serum, mostly to albumin. in patients with suspected increased free frac tion, it is more a ppropriate to moni tor the free concentration of phenytoin in serum (Baird-Lambert et al 1987: Perucca 1984: Peterson et al 1982: Rimmer et al 1984). 1987: Banh et al 1976: Perucca 1980: Rimmer et a1.…”
Section: Monitoring Free Pltenyto;n Concentrationmentioning
confidence: 99%